Religious Affairs Office in Providing Prime Services for the Community - Dodi Irama; Zudan Arief Fakrulloh; Ahmad Redi (Publikasiku, 2023)
Marriage according to Law no. 1 of 1974 concerning marriage is an inner and outer bond between a man and a woman to live a happy and eternal household based on Belief in the One and Only God. Marriage is a high honor and respect for the dignity given by Islam specifically for humans. Marriage is a process that must be followed by everyone to preserve offspring. In addition, marriage, as a process of perfecting half of religion, is also carried out as an effort to prevent adultery, to create peace and tranquility for the soul concerned, and peace for the family and society. A qualitative approach was used in this study to know the quality of services provided by the KUA Wonosalam in the registration and registration of marriages to achieve excellent service. The efforts of the Demak City Government to improve marriage management services at the Wonosalam Religious Affairs Office (KUA) are by trying to apply excellent service quality to every officer at the Wonosalam KUA. The Quality of Administrative Services for marriage registration at KUA Eonosalam is based on wholehearted service provided to the community, namely by applying the Tangible, Reliability, and Assurance dimensions in the indicators of infrastructure facilities and guarantees on time because there are still inadequate facilities and there are obstacles that hinder the administrative service process this KUA. Service has been said to be good in the Responsiveness and Empathy dimensions in terms of speed and accuracy of service and ease of good communication. Even though there are still some obstacles, the efforts that have been made are to improve the network they had